Some questions of polytechnic preparationteachers of labour studies (Pedagogy of Higher and Secondary Education, 2012)
Nedashkovsky Y., Kuchma А. Some questions of polytechnic preparationteachers of labour studiesSome aspects of polytechnic preparation of teachers of labour studies are resulted in part of the use of intersubject connections and computer technologies.
Keywords: computer technologies; tool; technical disciplines; intersubject knowledges; drafts